ANALISIS PENGARUH BRAND IMAGE, SERVICE QUALITY, PRODUCT QUALITY, PRICE, DAN SITUATIONAL FACTORS TERHADAP KEPUASAN PELANGGAN KENTUCKY FRIED CHICKEN (KFC) DI BG JUNCTION SURABAYA (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2009)
Result of research to the 60 pepoles customer Kentucky Fried Chicken (KFC) in BG Junction Surabaya indicates. that: (1) Customer satisfaction Kentucky Fried Chicken (KFC) in BG Junction Surabaya relative is higher (2). Brand image, service quality, product quality, price, and situational factors as partial and simultaneous proven have positive influence and significant to satisfaction Kentucky Fried Chicken (KFC) in BG Junction Surabaya (3). At Kentucky Fried Chicken (KFC) in BG Junction Surabaya, product quality has biggest influence to customer satisfaction.